One-Phototransistor-One-Memristor Array with High-Linearity Light-Tunable Weight for Optic Neuromorphic Computing - Dang, Bingjie (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2022 Wiley-VCH GmbH.